MICROBIOCENOSIS DISORDERS PROVOKE OXIDATIVE STRESS AS A SIGNIFICANT PATHOGENETIC FACTOR IN NON-ALCOHOLIC STEATOHEPATITIS COMBINED WITH ISCHEMIC HEART DISEASE - Skrypnyk, I.M.; Ohanisyan, E.V.; Maslova, G.S.; Neporada, K.S.; Shaposhnyk, O.A.; Prykhodko, N.P. (World of Medicine and Biology, 2025)
The study presents the results of our own research evaluating the impact of intestinal microbiocenosis disorders on oxidative stress activity and the degree of dyslipidemia in patients with combined non-alcoholic fatty liver disease and ischemic heart disease. The study included 44 patients with non-alcoholic steatohepatitis and concurrent ischemic heart disease. Patients were divided into two groups based on the presence of intestinal microbiocenosis disruptions. The findings demonstrate that under these comorbid conditions, microbiocenosis disturbances are characterized by: reduced lactobacilli counts in 95 % of patients, decreased bifidobacteria levels in 90.9 %, lower total Escherichia coli counts in 50 % of patients. A decrease in the total amount of Escherichia coli is associated with the emergence of opportunistic microflora. Under conditions combining non-alcoholic steatohepatitis and ischemic heart disease, impaired gut microbiota composition exacerbates the severity of dyslipidemia and triggers the production of reactive oxygen species with depletion of antioxidant defense enzymes. This is characterized by an increase in thiobarbituric acid-reactive substances (TBARS/TBA-reactants) levels alongside a simultaneous decrease in superoxide dismutase activity compared to normal gut microbiota composition.
Keywords: non-alcoholic steatohepatitis; ischemic heart disease; gut microbiota (microbiocenosis); oxidative stress; antioxidant defense; dyslipidemia